2015
DOI: 10.1177/2325967115607434
|View full text |Cite
|
Sign up to set email alerts
|

Predictors for Surgery in Shoulder Instability

Abstract: Background:Shoulder instability is a common cause of pain and dysfunction in young, active patients. While studies have analyzed risk factors for recurrent instability and failure after instability surgery, few have examined which variables are associated with initial surgery in this patient population.Purpose:To identify variables that may be associated with surgical intervention in patients with shoulder instability in the context of the FEDS (frequency, etiology, direction, severity) classification, a syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…In patients with SI, the ability to participate in sports-related activities is often inhibited, resulting in decreased quality of life [4]. Due to high recurrence rates and unsatisfactory outcomes after non-operative rehabilitation [6, 7], more than 60% of patients choose surgical treatment [8].…”
Section: Introductionmentioning
confidence: 99%
“…In patients with SI, the ability to participate in sports-related activities is often inhibited, resulting in decreased quality of life [4]. Due to high recurrence rates and unsatisfactory outcomes after non-operative rehabilitation [6, 7], more than 60% of patients choose surgical treatment [8].…”
Section: Introductionmentioning
confidence: 99%
“…Anterior shoulder instability (SI), which often develops following primary shoulder dislocation, is a common cause for reduced performance that impairs quality of life of young, active individuals. 1 Incidence rate of shoulder dislocation have been reported to be as high as 2.8% in a 9-month follow-up of 4141 healthy military cadets, 2 with 80.3% diagnosed for anterior shoulder dislocation. Recurrent shoulder dislocation, or SI, may develop in more than 55% of patients who sustained anterior shoulder dislocation.…”
mentioning
confidence: 99%
“…3,5,6 Retrospective data of patients with SI from 3 separate institutions in the United States indicated that over 60% underwent surgical treatment. 1 Surgical treatment is more common in younger patients who have experienced several dislocations, or those who were injured during sports activity. 1 Several surgical options are available for SI.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Anterior glenohumeral instability has been recognized as a common ailment for individuals of all demographics 1 . Its prevalence is approximately 1.7% of the population 2 .…”
mentioning
confidence: 99%